2021
DOI: 10.3390/ijms22094882
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Stress Alters the Secondary Metabolic Profile of M. sativa, M. arborea and Their Hybrid (Alborea)

Abstract: Increased soil salinity, and therefore accumulation of ions, is one of the major abiotic stresses of cultivated plants that negatively affect their growth and yield. Among Medicago species, only Medicago truncatula, which is a model plant, has been extensively studied, while research regarding salinity responses of two important forage legumes of Medicago sativa (M. sativa) and Medicago arborea (M. arborea) has been limited. In the present work, differences between M. arborea, M. sativa and their hybrid Albore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In addition, the increase in the activities and gene expression of SOD, CAT, APX, POX, and glutathione reductase (GR) in Hordeum vulgare roots five days after a treatment with 200 mM NaCl was correlated with H 2 O 2 detoxification [38]. The accumulation of secondary metabolites, such as saponins and lignans that have antioxidant capacity, in Medicago sativa and Medicago arborea roots exposed to 100 mM NaCl for 10 days increased salt stress tolerance [39]. In Olea europaea, long exposure of roots to 75 and 100 mM NaCl induced the accumulation of polyphenols and the increase of TAA, which was related to protection against salinity stress [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase in the activities and gene expression of SOD, CAT, APX, POX, and glutathione reductase (GR) in Hordeum vulgare roots five days after a treatment with 200 mM NaCl was correlated with H 2 O 2 detoxification [38]. The accumulation of secondary metabolites, such as saponins and lignans that have antioxidant capacity, in Medicago sativa and Medicago arborea roots exposed to 100 mM NaCl for 10 days increased salt stress tolerance [39]. In Olea europaea, long exposure of roots to 75 and 100 mM NaCl induced the accumulation of polyphenols and the increase of TAA, which was related to protection against salinity stress [40].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the secondary metabolism provides specialized metabolites that facilitate the salinity stress response through such mechanisms as antioxidant synthesis pathways for ROS scavenging and the reduction of oxidative damage [ 57 , 86 ]. A recent Fourier transform mass spectrometry LTQ orbitrap (FTMS)-based metabolomics study by Sarri and colleagues [ 89 ] found that secondary metabolites from saponins and hydroxycinnamic acids play a significant role in increased salinity-stress tolerance in Medicago sativa and Medicago arborea species. Similar findings were reported by Cai and co-workers [ 90 ], who found differential accumulation of secondary metabolites in salt-stressed plants compared to controls as determined through an HPLC-triple TOF-MS/MS.…”
Section: Current Applications Of Plant Metabolomics In Crop Improvementmentioning
confidence: 99%
“…Increased accumulation of saponin was observed in the leaves of Quillaja brasiliensis when exposed to abiotic elicitors such as salicylic acid, jasmonic acid, UV light and mechanical damage [73]. Furthermore, saponins might play a key role in plant salinity tolerance [74]. With inevitable climate changes in the frequency and severity of drought, further research is necessary to unravel the molecular mechanism of saponin fluctuation in response to environment changes, leading to tolerance toward stressors.…”
Section: Regulation Of Saponin Biosynthesismentioning
confidence: 99%